1996
DOI: 10.1128/jvi.70.2.985-991.1996
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and characterization of a replicase complex in rotavirus-infected cells by using a monoclonal antibody against NSP2

Abstract: Replication of the rotavirus genome involves two steps: (i) transcription and extrusion of transcripts and (ii) minus-strand RNA synthesis in viral complexes containing plus-strand RNA. In this study, we showed evidence for the importance of the viral nonstructural protein of rotavirus, NSP2, in the replication of viral RNAs. RNA-binding properties of NSP2 were tested by UV cross-linking in vivo (in rotavirus-infected MA104 cells and recombinant baculovirus-expressing NSP2-infected Sf9 cells). In rotavirus-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…Indeed, earlier studies have indicated that NSP2 is a component of viral replication intermediates, interacts with the RdRP VP1, and is bound to partially replicated RNA, features that are consistent with the direct participation of NSP2 in (−)-strand synthesis. 5,[11][12][13] One possibility is that soon after (−)-strand initiation, the nascent RNA product interacts with NSP2 in such a way that its 5′ end enters into one of the clefts of an octamer, where it engages the active site. This interaction may anchor the nascent (−) strand as the RdRP carries out elongation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, earlier studies have indicated that NSP2 is a component of viral replication intermediates, interacts with the RdRP VP1, and is bound to partially replicated RNA, features that are consistent with the direct participation of NSP2 in (−)-strand synthesis. 5,[11][12][13] One possibility is that soon after (−)-strand initiation, the nascent RNA product interacts with NSP2 in such a way that its 5′ end enters into one of the clefts of an octamer, where it engages the active site. This interaction may anchor the nascent (−) strand as the RdRP carries out elongation.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] These proteins are also components of the replication intermediates that synthesize dsRNAs in viroplasms. 5,11,12 The association of NSP2 with such intermediates may be mediated by interaction with the viral RNA-dependent RNA polymerase (RdRP), VP1. 13 NSP2 is a basic protein (M r = 35,000) that selfassembles into stable doughnut-shaped octamers, formed by the tail-to-tail interaction of two tetramers (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…NSP2 is encoded by the 8th gene segment in SA11 strain of rotavirus. It is an essential nucleating protein of viroplasms, which function as viral factories, where viral genome replication and assembly of double-layered particles (DLPs) take place [89]. Its interaction with NSP5 leads to viroplasm formation [90].…”
Section: Non-structural Protein Nsp2mentioning
confidence: 99%
“…4.1(b1)} [94]. It possess non-specific sequenceindependent RNA-binding activity and helps in efficient viral mRNA replication in combination with the viral polymerase complex [89,[94][95][96]. NSP2 also possesses Mg 2+ -dependent NTPase, helix-unwinding, and NDP kinase activities [96][97][98].…”
Section: Non-structural Protein Nsp2mentioning
confidence: 99%
“…Therefore, a localization to the exterior of the factory may represent an organized progression of virus maturation from the interior of the viroplasm to the exterior. However, things are probably not that straightforward because VP6 is also part of the viral RNA complex along with NSP2 (Aponte et al, 1996) which, as noted above, is localized to the center of the viroplasm.…”
Section: B Virus Nonstructural Proteins Determine Orthoreovirus Factmentioning
confidence: 99%